Propuesta para la creación de una empresa exportadora de tuna roja a Londres-Reino Unido - Méndez Guerrón, Alexis Israel (2024)
The present integration work proposes the establishment of a company dedicated to exporting red tuna to London, United Kingdom, capitalizing on its nutritional properties and the growing demand in international markets. The aim is to implement a sustainable and efficient business model that meets the quality standards of London consumers. Through a detailed analysis of the target market, financial viability, and logistical strategies, the intention is to demonstrate the economic and commercial potential of red tuna, contributing to the agricultural and economic development of the Valle del Chota, a region with large tuna plantations in Imbabura. Additionally, this project aims to promote the diversity of tropical fruits from Valle del Chota, benefiting the Afro-American population and positioning the company as a pioneer in red tuna exportation from Ecuador to London, strengthening its presence.